Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Guru pada Sekolah Menengah Islam Terpadu Boarding School Sukabumi - Helmi Ahmadi; Samsuri Samsuri; Titiek Tjahja Andari (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
The purpose of this study was to determine the effect of work motivation and work discipline on teacher performance at the Integrated Islamic High School Boarding School Sukabumi. The questionnaire was distributed to 36 respondents, in this study the approach used was quantitative, descriptive and verifiative research types and used surveys. The questionnaire uses validity tests, reliability tests and classical assumption tests. Analysis of research data using multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis and significant tests simultaneously and partially. The result of this study is that simultaneously work motivation and work discipline have a positive and significant effect on teacher performance at the Integrated Islamic High School Boarding School Sukabumi. Partially, work motivation has a positive and significant effect on teacher performance at the Integrated Islamic High School Boarding School Sukabumi, partially work discipline has a positive but not significant effect on teacher performance at the Integrated Islamic High School Boarding School Sukabumi.